Right hemisphere superiority for programming oculomotion: evidence from simple reaction time experiments - Sava, D; Liotti, M; Rizzolatti, G (Neuropsychologia, 1988)
Simple reaction times (RTs) to lateralized unstructured visual stimuli were measured in normal subjects while they were carrying out concomitant oculomotor tasks. Four tasks were used. In the first task, subjects had to find the correct path in a maze presented at the centre of a screen; in the second task, subjects had to follow a bright dot moved on a screen with variable direction, trajectory and velocity with their eyes; in the third task, the subjects had to follow a bright dot moved back and forth either horizontally or vertically along the same trajectory and at a constant velocity; in the fourth task, the subjects had to monitor the movement of a bright dot moved with variable direction, trajectory and velocity without moving the eyes. In all tasks, with the exception of the third, there was a selective lengthening of RTs mediated by the right hemisphere. It is concluded that the right hemisphere is dominant in programming eye movements.